The long-term effects of single and repeated subanaesthetic ketamine administration on regional cerebral blood flow in healthy dogs measured with 99mTc-HMPAO SPECT - Vlerick, Lise; Peremans, Kathelijne; Dockx, Robrecht; Audenaert, Kurt; Baeken, Chris; Saunders, Jimmy H; Polis, Ingeborgh (Psychiatry research. Neuroimaging, 2019)
• Repeated ketamine did not provoke prolonged cerebral perfusion alterations in dogs.• Ketamine increased cerebral perfusion in parietal, occipital and thalamic regions.• Clinical effects of repeated ketamine administration could not be assessed.• Results may differ in dogs with anxiety disorders. Subanaesthetic ketamine has recently been established as an effective and rapid treatment for major depressive disorder showing antidepressant effects for up to 1 week on average. The use of repeated ketamine infusions has been put forward to augment and to prolong the antidepressant response and increase the remission rates. The underlying neurobiological mechanisms responsible for ketamine's antidepressant effects remain unclear. Nevertheless, it has been shown, both in dogs and humans, that ketamine can alter neuronal perfusion and therefore neuronal function in brain regions involved in psychiatric and behavioural disorders. Consequently, the aim of the current placebo controlled study was to assess the long-term effects on cerebral perfusion of single and repeated subanaesthetic ketamine infusions in dogs. Twelve healthy, laboratory dogs were scanned at six different time points following single and repeated ketamine administration, using Single Photon Emission Computed Tomography with the radiotracer 99mTc-hexamethylpropylene amine oxime. We hypothesised that repeated infusions could lead to more prolonged perfusion alterations in brain regions critical for behaviour regulation. We found that repeated subanaesthetic ketamine administration did not result in more prolonged cerebral perfusion alterations compared to a single ketamine administration.